PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Pertambangan Subsektor Logam dan Mineral yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Hanny Liviana; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This study analyzes the effect of Good Corporate Governance (GCG) mechanism on the financial performance of metal and mineral mining companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The mining sector contributes significantly to Indonesia’s economy, yet remains vulnerable to commodity price fluctuations and external pressures such as the COVID-19 pandemic, the implementation of Good Corporate Governance is essential for financial performance. The independent variables are board size, independent commissioners, audit committee size, and institutional ownership; financial performance is measured using Return on Assets (ROA). A quantitative approach was applied using secondary data from annual reports and audited financial statements gathered through documentation. The sample was determined via purposive sampling, produced 7 companies with 35 total data observations analyzed using multiple linear regression. The F-test results indicate the four variables have no significant joint effect on ROA. Partially, the proportion of independent commissioners shows a significant positive effect, while board size, audit committee size, and institutional ownership are not significant. The study concludes that independent oversight quality matters more than other corporate governance mechanisms.